The complexity of home-based rehabilitation technology implementation for post-stroke motor rehabilitation in the Netherlands - Karlijn E. te Boekhorst; Sanne J. Kuipers; Gerard M. Ribbers; Jane M. Cramm (BMC Health Services Research)
Abstract Background Rehabilitation technology is a growing field, but the sustainable implementation of these technologies, particularly in home settings, is lacking. The aim of this study was to explore the factors influencing the uptake of stroke rehabilitation technology among various stakeholders, including developers, healthcare professionals, individuals who had strokes, strategic experts, management and innovation staff, health insurers, and the National Health Care Institute. Methods In total, 22 semi-structured interviews were conducted with a purposive stakeholder sample. The Non-adoption, Abandonment, Scale-up, Spread, and Sustainability (NASSS) framework was used as the theoretical basis for the interview design. The interview content was analysed to generate (sub)themes representing factors influencing the implementation of home-based rehabilitation technology. These (sub)themes were organised according to the NASSS framework domains to ensure a systematic and theoretically grounded analysis. Results Ten influencing factors emerged, nine of which fell within six of the seven NASSS domains. These factors include: (1) the unpredictable aftermath of stroke, (2) technology (mis)alignment with care delivery processes and end users’ preferences, (3) disparities in the assessment of technology’s value, (4) differences in commercial and university developers’ interests, (5) patient group capabilities, (6) perceived workload, (7) formal implementation plans in rehabilitation centres, (8) laws and regulations, and (9) the financial system. The factor that did not align with a single NASSS domain was: (10) the fragmentation of responsibilities among diverse stakeholders. Conclusion This study shows that the sustainable implementation of home-based rehabilitation technology faces several challenges across multiple domains of the NASSS framework. Effective collaboration among stakeholders is crucial for addressing these challenges but is currently hindered by fragmented responsibilities. To improve collaboration, it is essential to clearly define the roles and responsibilities of all stakeholders. Additionally, national-level policies adopting a systems approach are necessary to align these responsibilities and foster effective collaboration.